PENENTUAN AKTIVITAS TABIR SURYA DAN ANTIOKSIDAN EKSTRAK ETANOL BENALU (Henslowia frutescens) INANG JERUK BALI SECARA IN VITRO - Henny Nurhasnawati; Rusdiati Helmidanora; Yullia Sukawaty; Andri Priyoherianto; Elly Purwati (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2021)
Henslowia frutescens is a semi-parasitic plant, although considered harmful, it has medicinal and cosmetic potential. This plant has secondary metabolite compounds, namely phenolic compounds, flavonoids, saponins, tannins, and steroids which have high antioxidant activity. The purpose of this study was to determine the sunscreen activity of the ethanol extract of Henslowia frutescens based on the in vitro SPF (Sun Protecting Factor) value and to determine its antioxidant activity. The research stages included sampling, sampling, maceration extraction with 95% ethanol, yield calculation, phytochemical screening, sunscreen activity test based on SPF value, and antioxidant activity test. Data analysis was carried out descriptively based on the measurement results processed according to the calculation formula. The results showed that the sunscreen activity of the ethanol extract of Henslowia frutescens based on the in vitro SPF value was 14.57 - 25.20 with moderate protection category. The antioxidant activity of the ethanol extract of Henslowia frutescens showed a very strong category with an IC value of 22.82 Ã‚Â± 1.33.